Memory deficits correlate with tau and spine pathology in P301S MAPT transgenic mice. Issue 7 (17th November 2014) - Xu, Hong; Rösler, Thomas W.; Carlsson, Thomas; de Andrade, Anderson; Bruch, Julius; Höllerhage, Matthias; Oertel, Wolfgang H.; Höglinger, Günter U.
<x xml:space="preserve">Abstract</x> Aim P301S MAPT transgenic mice (P301S mice) are a widely used model of frontotemporal dementia and parkinsonism linked to chromosome 17 with tau pathology (FTDP‐17‐tau). However, a systematic correlation between cognitive deficits and cellular tau pathology at different ages is still missing. Therefore, our study investigated memory deficits of P301S mice in relation to pathological tau species and dendritic spine pathology throughout adulthood. Methods We analysed P301S mice behaviourally with the novel open field, rotarod, and Morris water maze tests to measure deficits in locomotion, balance and cognition, respectively; immunohistochemically with different tau antibodies for specific tau species; and with Golgi staining for dendritic spine pathology. Results We confirmed the occurrence of locomotor deficits at an age of 5 months and newly report memory deficits from 2.5 months of age onwards. At this early age, MC1 and CP13, but not AT180 immunoreactivity, was prominent in the hippocampus of P301S mice. Neuronal cell loss in the hippocampus of P301S mice was not observed to occur till 6 months of age. However, there was a significant reduction in the density of dendritic spines from young adulthood onwards in hippocampal pyramidal neurones. Conclusion In P301S mice, memory deficits precede the onset of locomotor dysfunction and coincide with the appearance of conformationally changed, S202‐phosphorylated tau and reduced spine density in the absence of neuronal cell loss in the hippocampus. Our finding provides insights into the toxic effects of different tau species in vivo and may facilitate the development of new therapies against neurodegenerative tauopathies.